Cu2SnSe3 phase formation from different metallic and binary chalcogenides stacks using magnetron sputtering. (January 2023) - Zaki, M.Y.; Sava, F.; Simandan, I.D.; Buruiana, A.T.; Mihai, C.; Velea, A.; Galca, A.C.
Abstract: Cu2 SnSe3 (CTSe) is a polyvalent material that can be used as an absorber layer for thin film solar cells or as a starting layer for the synthesis of CZTSe or CZTSSe compounds. Obtaining CTSe single phase films with optimized properties for thin film solar cells is a difficult task. A systematic study using both metallic and binary chalcogenides precursors for the formation of the CTSe phase was not performed. The films consisting of four different stacks (Sn, SnSe2 , Sn2 Se, and SnSe2 2 Se) were prepared by magnetron sputtering on soda lime glass (SLG) and molybdenum (Mo) coated SLG substrates, followed by annealing at 550 °C under Sn + Se atmosphere. X-ray diffraction and Raman spectroscopy results indicated the formation of a single CTSe phase in most of the stacks deposited on both substrates. Scanning electron microscopy images showed compact surfaces with large grains in the films deposited on Mo substrate, while the films on SLG have more voids on their surfaces. The elemental analysis measured by energy dispersive spectroscopy revealed stoichiometric films on Mo, and copper and tin rich compositions on SLG substrates. The band gap values inferred by conventional spectroscopy are between 0.81 and 1.95 eV. It was found that the SnSe2 and Sn2 Se stacks are preferred for the formation of a single CTSe phase, with dense surface morphology, a stoichiometric composition, and an optimal absorber layer band gap. This study opens the way to comprehend the formation reactions during the selenization of metallic and binary chalcogenides precursors towards the optimization of kesterite absorber for photovoltaic device fabrication. Highlights: Different stacks were prepared by MS using Cu, Cu2 Se, Sn and SnSe2 targets. Stacks were deposited on SLG and Mo substrates and annealed at 550 °C. Two metals or a metal and a binary chalcogenide lead to single phase CTSe films. The SnSe2 or Sn2 Se stacks have the best properties for absorber layers.